Carbide phases synthesised from C/Mo powder compacts at specified sub-stoichiometric ratios by solar radiation heating to temperatures between 1600 C and 2500 C - Granier, Bernard (2010)
There are a number of distinguishable carbide phases in the binary Mo-C system depending on C/Mo ratio as well as on temperature. In a preceding work published in this journal, carbide formation performance for graphite/molybdenum powder mixtures at specified levels of substoichiometric C/Mo atom ratio (C/Mo = 1/1, 3/4, 2/3 and 1/2) by exposure to concentrated solar radiation in a solar furnace at PROMESCNRS in Odeillo (France) was reported at a target temperature 1900 C. In the present work, the similar carbide synthesis experiments were carried out at 1600 C as well as at temperature exceeding 2500 C. The target temperature setting was adjusted by controlling the downward deviation of the test piece top surface position from the exact focal spot of the parabolic mirror concentrator located above. In this solar furnace at PROMES-CNRS, temperature of the test piece was raised from ambient temperature to the target temperature within fractions of a second. Reaction products detected were hexagonal -MoC1 x and -Mo2C (high temperature sub-carbide phase) depending on the C/Mo ratio in the starting material as well as on the processing temperature. No evidence of formation of cubic -MoC1 x was detected by X-ray diffraction analysis for any test piece examined.